Exploring students’ readiness on English language blended learning / Fazlinda Hamzah ... [et al.] - Hamzah, Fazlinda; Soo, Yew Phong; Sharifudin, Mohd Azlan Shah; Mohd Zain, Zainab; Rahim, Mahdalela (Universiti Teknologi MARA, 2020)
Blended learning approach has gained popularity around the globe and blended English language teaching has become a matter of considerable interest. Many higher education institutions have adopted the approach, and this raised a question of readiness among the students involved. The study aimed at investigating the students’ readiness on English language blended learning. A total of 137 students of different courses from a public university in Melaka participated in the study. They were asked to answer a questionnaire which involved five aspects to measure the students’ readiness on English language blended learning such as technical abilities, technological accessibility, self-directed learning, attitude towards traditional classroom setting and attitude towards blended classroom setting. Six students were then selected to be involved in semi-structured interviews to identify students’ views on English language blended learning. The study found out that students have low levels of readiness on English language blended learning in which they scored 3.28 to 3.54 in attitude towards blended classroom settings compared to their scores in attitude towards traditional classroom settings which are all above 4.00. The interviews revealed the reasons behind the results obtained from the questionnaire and one of them is that they enjoy learning English in a traditional classroom since face to face communication with their instructors allows them to remember better as well as enables them to gain more in-depth understanding of a lesson.